Reasoned opinion on the modification of the existing MRLs for ametoctradin in various commodities - European Food Safety Authority (EFSA Journal)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, The Netherlands, hereafter referred to as the evaluating Member State (EMS), received an application from the company BASF SE to modify the existing MRL for the active substance ametoctradin in leek and to set import tolerances for ametoctradin in potatoes, tropical root and tuber vegetables, onions, garlic, shallots, spring onions, aubergines, okra, gherkins, courgettes, cucurbits (inedible peel), broccoli, head cabbage, Chinese cabbage, scarole, cress, land cress, rucola/rocket, red mustard, leaves and sprouts of Brassica spp., spinach, beet leaves, purslane, celery, fennel, and hops. In order to accommodate the intended use of ametoctradin on leek in the Netherlands, and in order to accommodate the authorized uses in the United States and Canada on other crops under consideration, the EMS proposed to raise the existing MRLs in all crops (and also in lettuce), except in tomatoes and peppers. The EMS drafted two evaluation reports in accordance with Article 8 of Regulation (EC) No 396/2005, which were submitted to the European Commission and forwarded to EFSA. The submitted residue data are sufficient to derive the MRL proposals and to support the proposed residue data extrapolations for all the crops under consideration, except for spring onion. The submitted residue data indicated no need to modify the existing EU MRLs for tomatoes and peppers. Adequate analytical enforcement methods are available to control residues of ametoctradin in the commodities under consideration at the validated LOQ of 0.01 mg/kg. EFSA concludes that the uses of ametoctradin on the crops under consideration will not result in a consumer exposure exceeding the toxicological reference value and therefore will not pose a public health concern.